Three cases of catecholaminergic polymorphic ventricular tachycardia with prolonged QT intervals including two cases of compound mutations. Issue 3 (6th April 2018) - Saito, Aki; Ohno, Seiko; Nuruki, Norihito; Nomura, Yuichi; Horie, Minoru; Yoshinaga, Masao
Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is one of the leading causes of sudden arrhythmic death in the young. The QT interval in CPVT patients is typically within the normal range. However, those with prolonged QT interval have often been diagnosed with mutation‐negative long QT syndrome (LQTS). We report three CPVT patients with prolonged QT interval. Case 1 and 2 were diagnosed as LQTS at first. Genetic test using next‐generation sequencing (NGS) revealed RyR2 mutations. We should consider genetic test using NGS to identify the genes responsible for CPVT in mutation‐negative LQTS.